An anti-racist feminist analysis of power: a case study of a group of African women in an Eastern Cape township - Jackson, Carey-Ann (Rhodes University, Faculty of Humanities, Department of Psychology, 1995)
It is argued that South African feminism in the 1990's risks sabotaging itself as a movement and as a form of social critique because it has (1) not completely eradicated key positivist elements from its ontology and epistemology; (2) inadequately examined a crucial issue in an emancipatory social science, namely power; (3) increasingly opted for relativist and pragmatist perspectives in theorising women's oppression and social transformation. It is further argued that the over-reliance on relativism, standpoint theory and pragmatism is problematic for contemporary feminism. As an alternative, Bhaskar's transformational analysis of power in combination with an anti-racist feminism and social psychology is used to provide a robust framework within which complex social issues may be addressed. In this study, 16 female participants were interviewed about their experiences of living in an impoverished township. Themes identified in the data suggested that the theoretical perspectives used in the study provided insights into the subtleties and complexities of the operation of power in society. These insights enabled productive understanding of the strengths and weaknesses of development initiatives and political decision-making processes in the community, and the survival strategies of its women. It is hoped that research work of this sort could make a real contribution to the ongoing women's emancipation struggle in Port Alfred and similar communities.
Keywords: Power (Social sciences) -- South Africa; Feminism -- South Africa; Feminist theory -- South Africa; Women, Black -- Employment -- South Africa; Women, Black -- South Africa -- Social conditions